A class of rough multiple objective programming and its application to solid transportation problem - Tao, Zhimiao; Xu, Jiuping (Information sciences, 2012)
This paper establishes a rough multiple objective programming model for a solid transportation problem. Furthermore, a general model for rough multiple objective programming problem is presented. Properties of the feasible and efficient solutions of rough multiple objective programming problems are investigated. In addition, compromise solutions are obtained by using the interactive fuzzy satisfying method. To solve the rough multiple objective solid transportation problem, the rough simulation-based genetic algorithm is proposed, in which the rough simulation is embedded into the genetic algorithm. Finally, an application of the solid transportation problem at Xiluodu Hydropower Station is provided as an illustration.